Diagnostic and Therapeutic Procedures in Gastroenterology An Illustrated Guide (Clinical Gastroenterology, 2018)
This new edition provides a comprehensive overview of procedures for the gastrointestinal tract. The volume describes the indications, contraindications, and precise method of a procedure, under normal anatomical conditions and when the gastrointestinal tract is surgically altered. In addition to revised chapters from the previous edition, the latest edition features new chapters that cover such topics as endoscopic accessories, cleaning and disinfecting gastrointestinal endoscopes, tissue sampling, removal of foreign bodies, and confocal endoscopy and robotic endoscopy. Each chapter is also accompanied by photographs, diagrams, tables, and algorithms to precisely and easily display complex information. Written by leading authorities from around the globe, Diagnostic and Therapeutic Procedures in Gastroenterology: An Illustrated Guide, Second Edition is a valuable resource for gastroenterologists, primary care physicians, and gastroenterology fellows in training who treat and manage patients with gastrointestinal disorders.